2019
DOI: 10.1029/2019jd031007
|View full text |Cite
|
Sign up to set email alerts
|

The Land‐Sea Breeze of the Red Sea: Observations, Simulations, and Relationships to Regional Moisture Transport

Abstract: Unique in situ observations of atmospheric conditions over the Red Sea and the coastal Arabian Peninsula are examined to study the dynamics and regional impacts of the local land‐sea breeze cycle (LSBC). During a 26‐month data record spanning 2008–2011, observed LSBC events occurred year‐round, frequently exhibiting cross‐shore wind velocities in excess of 8 m/s. Observed onshore and offshore features of both the land‐ and sea‐breeze phases of the cycle are presented, and their seasonal modulation is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…Figure 6a shows the diurnal cycle climatology (2015/16) of station-measured surface wind speed at the study site. The surface winds reach a peak around noon UTC (15:00 local time) for all seasons except winter, consistent with the results of Davis et al (2019). The aforementioned sea breezes cause these wind peaks in the afternoon.…”
Section: Surface Meteorologysupporting
confidence: 88%
See 3 more Smart Citations
“…Figure 6a shows the diurnal cycle climatology (2015/16) of station-measured surface wind speed at the study site. The surface winds reach a peak around noon UTC (15:00 local time) for all seasons except winter, consistent with the results of Davis et al (2019). The aforementioned sea breezes cause these wind peaks in the afternoon.…”
Section: Surface Meteorologysupporting
confidence: 88%
“…This warm air mass rises due to convection, creating a local low pressure at the surface. The cooler and more moist air over the Red Sea then flows towards the low pressure, thus forming sea breezes (Simpson, 1994;Miller et al, 2003;Davis et al, 2019). During the night, this flow is reversed to form land breezes, when the land surface temperature cools quicker than the sea surface temperature.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Later, it was shown that topography and surface inhomogeneity may lead to anticlockwise rotating hodographs (Alpert et al, 1984;Kusuda & Alpert, 1983). The time-dependent surface wind hodograph has been used as a mean to study and analyze sea-breeze dynamics and in some cases has demonstrated structural and rotational properties that are more complex than in the BSB model (Abatan et al, 2014;Ascario et al, 2018;Bajamgnigni Gbambie & Steyn, 2013;Coulibaly et al, 2019Coulibaly et al, , 2020Davis et al, 2019;Huang et al, 2016;Moisseeva & Steyn, 2014;Steyn & Kallos, 1992).…”
Section: 1029/2020jd033691mentioning
confidence: 99%